Social media addiction and academic performance in students at the Universidad Nacional de San Martín, Rioja, Peru - Mera Naval, Hugo Jaime (2026)
Objective. To determine the relationship between social media addiction and academic performance in students at the Universidad Nacional de San Martín, Rioja, Peru. Methods. The study used a quantitative approach, with a descriptive-correlational level and a non-experimental design. The sample was census-based and consisted of 266 students, who were administered two questionnaires; academic records were collected using a document analysis guide. Spearman’s rho test was used for data analysis. Results. The variable “social media addiction” was classified as moderate in 87.6% of cases. As for the variable “academic performance,” it was found to be at a moderate level. The correlation between these variables was -0.143. The two-tailed significance value was 0.020 and was therefore lower than 0.05. Conclusions. There is a significant relationship between “social media addiction” and “academic performance” in students at the Universidad Nacional de San Martín.